2006
DOI: 10.2298/mpns0612556g
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, pre-eclampsia and eclampsia: Monitoring and outcome of pregnancy

Abstract: Pregnancy-induced hypertension, pre-eclampsia and eclampsia are parts of the hypertensive syndrome which is a life-threatening condition both for mother and fetus. Apart from being associated with unpredictable onset, it is incurable, except by ending the pregnancy. Its incidence is approximately between 6 - 10% of pregnant women. There is no unique definition and classification of the hypertensive syndrome in pregnancy, i.e. they differ from one expert group to another. RISKS OF PREGNANCY-INDUCED HYPERTENSION… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Hypertensive disorder of pregnancy is considered to be a major worldwide problem and presents an increased risk of both maternal and perinatal mortality and morbidity [26,27]. Preeclampsia, a multisystem disorder partly of unknown aetiology specific to pregnancy [28], has been implicated as one of the main predisposing factors for intrauterine foetal growth restriction and prematurity [29].…”
Section: Low Birth Weight and Preterm Birthmentioning
confidence: 99%
“…Hypertensive disorder of pregnancy is considered to be a major worldwide problem and presents an increased risk of both maternal and perinatal mortality and morbidity [26,27]. Preeclampsia, a multisystem disorder partly of unknown aetiology specific to pregnancy [28], has been implicated as one of the main predisposing factors for intrauterine foetal growth restriction and prematurity [29].…”
Section: Low Birth Weight and Preterm Birthmentioning
confidence: 99%
“…Pregnancy induced hypertension is one of the major causes of maternal and fetal/neonatal morbidity and mortality. 10 In a study to determine risk factors, prevalence, epidemiological parameters and maternalperinatal outcome in pregnant women with hypertensive disorder, found that 24 cases of intrauterine fetal demise out of 255 cases and 10 fetuses died during intrapartum period. Perinatal mortality was found to be 144/1000 births.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-induced hypertension, pre-eclampsia and eclampsia are parts of hypertensive syndrome which is a life-threatening condition both for the mother and fetus [14]. Pregnancy itself is a state of increased oxidative stress, and the increase of the oxidative damage is considered important for the development of pregnancy complications such as PEE.…”
Section: Discussionmentioning
confidence: 99%